PRINSIP PENGENDALIAN PERANCANGAN TAMAN BERMAIN ANAK DI RUANG PUBLIK - Medha Baskara (http://arl.faperta.ipb.ac.id/, 2011)
Children playground is a place designed particularyfor children to play freely so they gain cheerfulness, joy and excitement. It also canbecome as a mean to develop their cognitive, social, physical, and emotional abilities. Children playgrounds managed by the government, private, schools and communities, currently do not have proper design standards to support the safety and health of users. Those which do not pay attention to safety, comfort, convenience, and health in the design is very risky causing accidents and further the main purpose of playing the game can not be achieved. Therefore, design control of children playground is required in order to minimize the negative impact of children playgroundand its facilities on children's safety and health. The design control also important to assure society that assigned functions of children playground workproperly. Criteria and indicators of children playground design are safety, health, comfort, convenience, security, and aesthetic. Components to be arranged in the design control of children playground are location, layout, game equipments, construction, and materials. This article reviews the design control of children playground and studies the case in Indonesia.